Bandgap Narrowing in Non‐Fullerene Acceptors: Single Atom Substitution Leads to High Optoelectronic Response Beyond 1000 nm. Issue 24 (28th June 2018) - Lee, Jaewon; Ko, Seo‐Jin; Seifrid, Martin; Lee, Hansol; Luginbuhl, Benjamin R.; Karki, Akchheta; Ford, Michael; Rosenthal, Katie; Cho, Kilwon; Nguyen, Thuc‐Quyen; Bazan, Guillermo C.
Abstract: Two narrow bandgap non‐fullerene acceptors (NBG‐NFAs), namely, COTIC‐4F and SiOTIC‐4F, are designed and synthesized for the fabrication of efficient near‐infrared organic solar cells (OSCs). The chemical structures of the NBG‐NFAs contain a D′‐D‐D′ electron‐rich internal core based on a cyclopentadithiophene (or dithienosilole) (D) and alkoxythienyl (D′) core, end‐capped with the highly electron‐deficient unit 2‐(5, 6‐difluoro‐3‐oxo‐2, 3‐dihydro‐1H‐inden‐1‐ylidene)malononitrile (A), ultimately providing a A‐D′‐D‐D′‐A molecular configuration that enhances the intramolecular charge transfer characteristics of the excited states. One can thereby reduce the optical bandgap ( E g opt ) to as low as ≈1.10 eV, one of the smallest values for NFAs reported to date. In bulk‐heterojunction (BHJ) OSCs, NBG‐NFA blends with the polymer donor PTB7‐Th yield power conversion efficiencies (PCE) of up to 9.0%, which is particularly high when compared against a range of NBG BHJ blends. Most significantly, it is found that, despite the small energy loss ( E g opt − e V OC ) of 0.52 eV, the PTB7‐Th/NBG‐NFA bulk heterojunction blends can yield short‐circuit current densities of up to 22.8 mA cm −2, suggesting that the design and application of NBG‐NFA materials have substantial potential to further improve the PCE of OSCs. Abstract : Two non‐fullerene electron acceptors (NFAs) featuring extremely narrow bandgaps (as low as 1.10 eV) are designed and synthesized. The NFAs in organic solar cells contribute broad external quantum efficiency responses in the near‐infrared region over 1000 nm, resulting in high power conversion efficiency of up to 9% with remarkable current density of 23 mA cm −2 .